2019
DOI: 10.1038/s41598-019-41706-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of p53 Isoform Expression on Survival in High-Grade Serous Ovarian Cancers

Abstract: High-grade serous ovarian carcinoma (HGSOC) is characterised by alterations in the p53 pathway. The expression levels of p53 isoforms have been shown to be associated with patient survival in several cancers. This study examined the predictive and prognostic effects of the expression levels of TP53 pre-mRNA splicing isoforms and TP53 mutations in tumour tissues in 40 chemotherapy responders and 29 non-responders with HGSOC. The mRNA expression levels from total p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 39 publications
2
25
2
Order By: Relevance
“…We next measured the levels of the TP53 transcripts in a cohort of 83 human breast tumours [26] using the ddPCR assays of TP53 transcript 5' and 3' ends described previously [8] (FL/∆40TP53_T1, FL/∆40TP53_T2, ∆133TP53 TP53 5' ends and the TP53α and TP53β 3' ends; Figure S2A). We found that the levels of FL/∆40TP53_T1 5' end had the highest correlation with the TP53α 3' end, and that the levels of the ∆133TP53 5' end had the highest correlation with TP53β 3'end, consistent with other studies ( Figure S2B [9,11,14,15]). The same 83 breast tumour RNA samples were then analysed using the multiplex long amplicon ddPCR assays described above, successfully quantifying the levels of the seven major TP53 transcripts across these tumours and importantly demonstrating that these assays can be used on RNA derived from tumour samples.…”
Section: Demonstration Of Tp53 Isoform Analysis In Breast Cancer Patisupporting
confidence: 92%
See 3 more Smart Citations
“…We next measured the levels of the TP53 transcripts in a cohort of 83 human breast tumours [26] using the ddPCR assays of TP53 transcript 5' and 3' ends described previously [8] (FL/∆40TP53_T1, FL/∆40TP53_T2, ∆133TP53 TP53 5' ends and the TP53α and TP53β 3' ends; Figure S2A). We found that the levels of FL/∆40TP53_T1 5' end had the highest correlation with the TP53α 3' end, and that the levels of the ∆133TP53 5' end had the highest correlation with TP53β 3'end, consistent with other studies ( Figure S2B [9,11,14,15]). The same 83 breast tumour RNA samples were then analysed using the multiplex long amplicon ddPCR assays described above, successfully quantifying the levels of the seven major TP53 transcripts across these tumours and importantly demonstrating that these assays can be used on RNA derived from tumour samples.…”
Section: Demonstration Of Tp53 Isoform Analysis In Breast Cancer Patisupporting
confidence: 92%
“…To date, the p53 field has predominantly used correlation analysis to try to draw inferential conclusions about which TP53 transcript 5' ends are associated with which 3' ends [11][12][13][14][15]. Our assays now provide the ability for researchers to detect and quantitate full length TP53 transcripts, without the need to draw inferential conclusions, and so can facilitate the understanding of TP53 isoform biology at a more comprehensive level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High tissue or serum total ∆133p53/TAp53 ratio is associated with poor overall and progression-free survival. [45] Ovarian cancer Total ∆133p53 mRNAs expression in mutant TP53 patients is associated with longer overall survival and disease-free survival [46] Total ∆133p53 mRNAs are associated with increased overall survival (and borderline disease-free survival) independently of TP53 mutation status [47] Renal cell carcinoma Wild-type tumors correlate with worse overall survival. Total ∆133p53 mRNAs are downregulated in WT tumors compared to mutant tumors and normal adjacent tissue [48] Breast cancer ∆133p53α mRNA is detected in tumor but not in normal tissue [6] ∆133p53β mRNA detection is associated with worse overall and disease-free survival [49] ∆133p53β protein is overexpressed in invasive tumor as compared to non-invasive ones [50] Glioblastoma ∆133p53β is elevated in glioblastoma malignant cells and is associated with immunosuppressive and chemoresistant environment [36] Prostate cancer ∆133p53β mRNA is elevated in tumor vs. non-neoplastic tissue and is associated with shorter progression-free survival [37] Melanoma Increased ∆133p53β mRNA expression is associated with poorer overall survival [51] The first part of the table displays the studies in which all three ∆133p53 mRNAs have been quantified as a whole, while the second part of the table displays the studies in which a single specific isoform has been identified.…”
Section: Colon Cancermentioning
confidence: 99%